ANALISIS PERBANDINGAN KINERJA REKSA DANA SYARIAH DENGAN KINERJA REKSA DANA KONVENSIONAL - Ervani Nur Sekarini; Istutik Istutik (Adbis: Jurnal Administrasi dan Bisnis, 2019)
This study aims to determine the difference between the performance of Islamic mutual funds with the performance of conventional, mixed type and fixed income mutual funds with sharpe ratio, treynor ratio and jensen ratio measurement methods. This type of research is quantitative research, where the source of the data used is secondary data. The population in this study are equity, mixed and fixed income mutual funds found on the official website of PT Bareksa Investment Portal, the sample used is conventional and sharia mutual funds issued by the same and active investment managers during 2015-2017. The data used in the form of Net Asset Value (NAV) data for 2014-2017, Jakarta Islamic Index (JII) and Composite Stock Price Index (CSPI), data on interest rates for Bank Indonesia Certificates (SBI) for the 2015-2017 period. The analytical method used is the Independent Sample t-test, with the SPSS program. The results showed that there was no significant difference between the performance of Islamic mutual funds and the performance of conventional, mixed, and fixed income types of conventional mutual funds by using sharpe ratio, treynor ratio and jensen ratio measurements.